Population dynamics in Kampong chicken and consequences for HPAI vaccination: results of a field trial in Java - Unger, Fred; Priyono, W.; Siregar, E.S.; Azhar, M.; Bett, Bernard K.; McLaws, M.; Jost, Christine; Mariner, Jeffrey C. (2012)
Until today HPAI in poultry is considered to be endemic in most of the Indonesian provinces since it was officially declared in 2004. Vaccination is used as one of the control strategies targeting layer and breeder farms but also Kampong (village) chicken. Limited information is available on the scope of off-take and replacement occurring in Kampong chicken populations under field condition and their effects on HPAI vaccination. To collate information on population dynamics in Kampong chicken, twelve communities with 300-500 chickens each have been enrolled in this trial. Chicken exit/entries as well as disease/mortality events were intensively monitored in weekly intervals. The trial was carried out between July 2008 and August 2009 in two Districts of Yogyakarta, Java. Results indicate that 39-44% of chickens were younger than two months of age over time and more than two-thirds of chickens were younger than four months, respectively. Adult chickens represented only 10% (male) and 20% (female) of the total population. Though overall population size within the selected communities was relatively stable, the number of chickens changed widely within age classes. In each observed quarter, there was a 43% or higher turnover of the population (43-72%). Observed changes were related to socio-cultural events such as holidays or begin of school. From our results we can conclude that approximately 40% of a natural backyard population will be un-vaccinated by 60 days after the onset of a vaccination campaign. Considering this high population turnover rate, even a quarterly vaccination regime including a booster round is required will have difficulty achieving effective flock immunity levels. This results in high costs, poses a significant logistical challenge and suggests mass vaccination is not a practical approach to sustained control of HPAI.